A presença do cinema na narrativa de Manuel Puig: uma análise das obras A traição de Rita Hayworth e The Buenos Aires affair - Trentin, Ludiani Retka (2020)
This research developed a comparative study between the Argentinian writer Manuel Puig’s Works Betrayed by Rita Hayworth and The Buenos Aires Affair. Even though there are many pieces of research developed about this author's works, the relevance of this work is justified for, although there is a narrow relation between cinema and literature, it couldn't be found any Brazilian studies which try to discuss the movie strategies used in literary writing, or which analyze the seventh art's influence in writing. Therefore, its objectives are: to research the movie procedures inserted in Argentinean literature and the way it can be found on both romance that introduces Puig’s two first writing cycles; and to verify the way cinema interferes in the diegesis, assisting the reader to understand the text through its intertextual relation. Especially, its critical-theoretical basis comprises Lourdes Pérez Villarreal (2001) and Carlos Dámaso Martínez (2017) with their studies about cinema and literature relation, Umberto Eco's theory of Hipotipose (2003), Ricardo Piglia (2016) who clarifies about the literary vanguards, and Coral Cruz (2014) who writes about the screenplays language. Jorgelina Corbatta’s theoretical work (2009) was the basis for discussions about Puig’s literary aesthetics, considering the creation of the personal and public myths at the Argentinean writer’s works. Finally, Maurício de Bragança’s study was used to outline the connection between fictional work and reality representation. Besides these authors, many other important researchers contributed to the development of this work in less quantity, but with the same relevance. It was verified that Manuel Puig wrote with authenticity, joining movie language to literature through imagery components - like photography, frame, and color, for example - sound and movement. His writing uses some techniques such as montage and voices overlap to rethink about the narrator’s condition and its unilateral position, reducing the descriptions so the reader can imagine what they are reading through their cultural knowledge. Besides, the descriptions tend to be less sentimental, which makes it similar to shoots from a movie camera. It was understood, in both analyzed books, that the cinema also interferes with the content, expanding the horizon of meaning, which, after all, offered to literature a possibility to aesthetics renew. So, the first novel explores how Hollywood Productions interfere in Coronel Vallejos’ families’ lives, as a role model for behavior and also as an escape from reality. On the other hand, the third novel inserts an intertextual relation with cinema as a way of questioning the content, engaging them so it can broaden the reader’s comprehension.